The Impact of the Secondary Market on Life Insurers' Surrender Profits - Gatzert, Nadine; Hoermann, Gudrun; Schmeiser, Hato (Journal of Risk and Insurance, 2009)
Life insurers often claim that the life settlement industry reduces their surrender profits and leads to an adverse shift in their portfolio of insured risks; that is, high risks remain in the portfolio instead of surrendering. In this article, we aim to quantify the effect of altered surrender behavior - subject to the health status of an insured - in a portfolio of life insurance contracts on the surrender profits of primary insurers. Our model includes mortality heterogeneity by applying a stochastic frailty factor to a mortality table. We additionally analyze the impact of the premium payment method by comparing results for annual and single premium payments.
WiSo-Import:2015-03-26:956
Keywords: -